Evaluating the utilization of public art capabilities in cultural-led regeneration (Case study: Oudlajan neighborhood) - mahmood ARVIN; Mahsa ghaneh; ahmad pourahmad (تحقیقات کاربردی علوم جغرافیایی)
Considering that today many cities of the country face problems such as problems of distressed urban fabric, in order to solve these problems, various solutions have been presented by experts and theorists, among which one can refer to regeneration. Regeneration has different approaches that have been studied in this research of the re-establishment of the cultural-led. The main objective of this research is to assess the utilization of the capabilities and abilities of public art in two permanent and temporary dimensions and the extent of the impact of public art on socio-cultural, physical and economic aesthetics in order to regeneration the distressed urban fabric of the Oudlajan neighborhood in Tehran. The present research is descriptive-analytical in terms of objective, applied. By studying the related studies of public art indices in two permanent dimensions (furniture, green space and moving plants, mural painting, restoration of the monument, cafes and restaurants, library, statue, element, entrance and bridge design) and temporary (street display, competitions, Exhibitions and festivals, artists' residences, workshops, sound, light and sound, video broadcasting). The statistical population of the questionnaire is the residents of the Oudlajan neighborhood. According to the population of the neighborhood, 16,943 people were selected using the Cochran formula, 384 as the sample size. To analyze the response of citizens, the analysis of structural equations in soft AMOS graphics has been used. The results show that permanent and temporary public art promotes economic development, the development of physical aesthetics and socio-cultural development in the Oudlajan neighborhood, among which permanent and most popular exhibitions are the highest in the cafes and restaurants, and the bridge has the least impact. In the interim animated film, the video playback index has the most impact and the least impact is the soundtrack.